Critical and Clinical Cartographies : Architecture, Robotics, Medicine, Philosophy - Radman, Andrej (New Materialisms : NEMA, 2022)
Discusses the newly emerging discourses between architecture and bio-medicineCritical and Clinical Cartographies rethinks medical and design pedagogies in the context of both the Affective and Digital Turns that are occurring under the umbrella of New Materialism. This collection is framed through Deleuze's symptomalogical approach which creates the ideal terrain for architecture and medical technologies of care to meet with robotics, alongside the newly emerging 'materialist landscape'.A number of questions emerge, which are addressed across the collection.What is the impact of the Digital Turn on the contemporary medical and architectural education and/or practice?How does the Posthuman Turn influence the possible convergence of medical and architectural education and/or practice?How has the biopolitical concept of care mutated under the proliferation of digital technology?How could medical research contribute to architectural design and how could design, in turn, contribute to the improvement of health care?"